A new species of Lepidodactylus (Squamata: Gekkonidae) from Umboi Island, Papua New Guinea - Kraus, Fred; Vahtera, Varpu; Weijola, Valter (Zootaxa, 2023)
We describe a new species of Lepidodactylus from Umboi Island, just to the west of New Britain. It is a member of the Lepidodactylus guppyi Group and can be distinguished from all other Melanesian Lepidodactylus by aspects of digital scalation, digital webbing, enlarged femoral/precloacal scales, and color pattern. It is genetically distinct from its closest congeners, and genetic and morphological data indicate that the new species is most similar among named species to Lepidodactylus guppyi from the Solomon Islands, but it diverged from this species and other close relatives approximately 8 MYA or longer at a time prior to the existence of the island that it now occupies. The new species is known from only three individuals collected on a single tree, and efforts to find more animals in what seemed good habitat nearby were unsuccessful. This duplicates the pattern of apparent rarity seen for many Lepidodactylus species. Sufficient habitat exists on Umboi Island for arboreal geckos, suggesting that the species is not actually endangered but is ecologically cryptic. However, lack of needed information leads us to assess this species’ conservation status as Data Deficient.